SVIATOSLAV HORDYNSKY AND POLISH LITERATURE - Мочернюк, Н. Д. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The various forms of reception of Polish literature in Hordynsky’s works are investigated in the article. The materials of analysis were literary and art studies of author, poetry and translations of author. Major attention is paid to the Hordynsky’s creative dialogue with Polish writer Josef Lobodovsky.